Plasma insulin-like growth factor 1, insulin-like growth factor binding protein 3, and risk of colorectal cancer: a prospective study in northern Sweden. (1st May 2002) - Palmqvist, R; Hallmans, G; Rinaldi, S; Biessy, C; Stenling, R; Riboli, E; Kaaks, R
Abstract : Background: Insulin-like growth factor 1 (IGF-1) has antiapoptotic and mitogenic effects on various cell types, and raised IGF-1 levels are increasingly being implicated as potential risk factors for cancer. Aims: To examine the relationship between IGF-1 and its major plasma binding protein, IGF binding protein 3 (IGFBP-3), and the risk of colorectal cancer. Methods: We conducted a case-control study nested within the Northern Sweden Health and Disease Cohort. IGF-1 and IGFBP-3 were measured in prediagnostic plasma samples from 168 men and women who developed cancers of the colon (n=110) or rectum (n=58), and from 336 matched controls. Results: Conditional logistic regression analyses showed an increase in colon cancer risk with increasing levels of IGF-1 (odds ratios (ORs) 1.00, 1.89, 2.30, 2.66; ptrend =0.03) and IGFBP-3 (ORs 1.00, 0.91, 1.80, 1.93; ptrend =0.02). Rectal cancer risk was inversely related to levels of IGF-1 (ORs 1.00, 0.45, 0.33, 0.33; ptrend =0.09) and IGFBP-3 (ORs 1.00, 0.75, 0.66, 0.49; ptrend =0.21). Mutual adjustments between IGF-1 and IGFBP-3 did not materially alter these relationships. Conclusions: These results support earlier findings of increased risk of colon cancer in subjects with elevated plasma IGF-1. Our results however do not support the hypothesis that the risk of rectal cancer could also be directly related to IGF-1 levels.